Knowledge of Posyandu Cadres in Carrying Out Roles for Stunting Prevention in Jarum Village, Klaten Regency - Soleha, Azza Rhohidatus; Umaroh, Ayu Khoirotul (PROMOTOR, 2025)
Background: Stunting is a chronic nutritional problem that has a serious impact on child growth and development and the quality of Indonesia's human resources. Posyandu cadres as the spearhead of health services in the community have an important role in efforts to prevent stunting. Objective: This study aims to describe the knowledge of posyandu cadres in carrying out their role for stunting prevention in Jarum Village, Bayat District. Methods: This study used a qualitative approach with a case study design. The data was collected through in-depth interviews with eight posyandu cadres and two key informants, namely puskesmas officers and village midwives. The validity of the data is tested through source triangulation. Results: The results of the study showed that most cadres had a good understanding of stunting, its causes, impacts, and prevention efforts. Cadres carry out their roles through nutrition education, growth monitoring, home visits, and PMT distribution. However, the implementation of the role still faces obstacles such as limited tools, lack of technical training, and communication challenges with the community. Conclusion: Sufficient cadre knowledge about stunting shows their strategic role in prevention. Cross-sectoral support, regular training, and facility improvements are needed to optimize the role of posyandu cadres at the community level.